Prototype and Design of Six Axis Robotic Manipulator - Pająk, Mateusz; Racław, Marcin; Piotrowski , Robert (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
The paper presents a design of six axis manipulator. The design consists of specially designed solutions for housing, planetary gearboxes and electronics. The manipulator is controlled by a supervisory control system. The use of a series of measuring elements allows to track the current position of each axis and use this to create a cascade control loop with velocity and acceleration feed-forward. The implemented control algorithm together with the microcontroller software allows to tune parameters of the controllers for both control loops: inner, related to the speed of the robot and outer, related to it’s position.